ISTEC - Library Linkage Initiative - De Giusti, Marisa Raquel (2018)
The LibLink Initiative focuses on academic and scientific information management. This means not only localization and bibliographic provision (sharing library collection) but also valuing and giving visibility to institutional production. To achieve these objectives, the initiative adapts current free access technologies and uses its own developments (Celsius 3), sharing them with its partners: information and statistics managers, tools for harvesting open resources, all of which allow ubiquitous information sharing, with the possibility of providing the partners with the resource in their usual work space.